Thin-layer chromatography : a modern practical approach - Wall, Peter E. (RSC chromatography monographs., 2005)
Thin-Layer Chromatography (TLC) is a modern, reliable tool that complements other chromatographic techniques. This book provides a practical guide to the basic principles, procedures and pitfalls on the practical application of TLC. Thin Layer Chromatography: A Modern Practical Approach offers a sequence of chapters following the steps of the technique as the chromatographer would follow them. The chapters provide a choice of sorbent best suited to the separation intended, followed by pre-treatment required for the sample, applying the sample to the sorbent layer, development procedure, visualisation and detection, and finally quantification. Imaging and hyphenation techniques are described. The reasons why recommendations are made for specific and more general methods are covered. The book also provides an overview of some recent developments in the field.